Determinants of Information Technology Investment Expenditure - Josua Panatap Soehaditama; Adler Haymans Manurung; Nera Marinda Machdar; Wastam Wahyu Hidayat (Greenation International Journal of Economics and Accounting, 2025)
Amid globalization, financial deregulation, and market volatility, banks aggressively adapt to maintain long-term competitive advantages. While digital transformation is non-negotiable, heavy capital allocations for Information Technology (IT) often face the "productivity paradox," where extensive spending does not automatically translate into immediate efficiency or output returns. Objective: This study aims to analyze the critical internal and external determinants of IT Investment Expenditure in the Indonesian banking industry. Methodology: Drawing upon the Resource-Based View (RBV) and Dynamic Capabilities Theory, this study utilizes panel data from commercial banks listed on the Indonesia Stock Exchange (IDX) and registered with the Financial Services Authority (OJK) from 2010 to 2023. The empirical framework corrects prior model discrepancies by formally treating Bank Risk as an independent control variable. Model selection was rigorously evaluated using the Chow, Hausman, and Lagrange Multiplier (LM) tests, validating the Fixed Effect Model (FEM) as the most robust specification. Results: The empirical findings demonstrate that Leadership and Efficiency (BOPO) have a statistically significant positive impact on IT Investment Expenditure. Conversely, Bank Size exhibits a statistically significant negative effect. Client-Based variables, Bank Risk (NPL), and the COVID-19 pandemic dummy do not show a statistically significant direct impact on IT expenditures. Conclusion: The findings suggest that smaller banking institutions bear a disproportionately higher financial burden relative to their asset size to keep pace with technological changes, whereas larger banks successfully exploit structural economies of scale in their IT infrastructure deployment.